2018
DOI: 10.3847/1538-4357/aa9c80
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Atmospheres on HD 219134 b and c

Abstract: We analyze the interiors of HD219134b and c, which are among the coolest super-Earths detected thus far. Without using spectroscopic measurements, we aim at constraining if the possible atmospheres are hydrogen-rich or hydrogen-poor. In the first step, we employ a full probabilistic Bayesian inference analysis to rigorously quantify the degeneracy of interior parameters given the data of mass, radius, refractory element abundances, semimajor axes, and stellar irradiation. We obtain constraints on structure a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 63 publications
1
29
1
Order By: Relevance
“…Such thin atmospheres cannot be of primordial H/He, since atmospheric escape can efficiently erode thin H/He layer on short time-scales. An atmosphere of H/He is only stable against evaporative loss if it would be significantly thicker than the theoretical minimum threshold-thickness (Dorn & Heng 2018), which is 0.18 R p for TOI-141b. The threshold-thickness corresponds to the amount of gas (H 2 ) that is lost on short time-scale (here we use 100 Myr).…”
Section: Interior Characterization: Results and Discussionmentioning
confidence: 89%
“…Such thin atmospheres cannot be of primordial H/He, since atmospheric escape can efficiently erode thin H/He layer on short time-scales. An atmosphere of H/He is only stable against evaporative loss if it would be significantly thicker than the theoretical minimum threshold-thickness (Dorn & Heng 2018), which is 0.18 R p for TOI-141b. The threshold-thickness corresponds to the amount of gas (H 2 ) that is lost on short time-scale (here we use 100 Myr).…”
Section: Interior Characterization: Results and Discussionmentioning
confidence: 89%
“…(Gillon et al 2017) also consider the possibility of a thick H-dominated atmosphere and/or water layers to explain planet b's lower density. Considering evaporative loss, Dorn & Heng (2018) conclude that the possible atmospheres are unlikely to be dominated by H but gas of heavier mean molecular weight, i.e., outgassed from the interior.…”
Section: Previous Studies On Hd219134 B and Cmentioning
confidence: 94%
“…The two rocky planets in the K-dwarf system HD219134 (Gillon et al 2017) are curious in that they do not follow the same mass-radius trend, but show a 10% density difference. Dorn & Heng (2018) have shown that their interiors can be explained by using stellar abundance constraints on refractory elements. The lower bulk density of planet b was suggested to be due to a secondary atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…TOI-402.02 hosts a thick atmosphere that is likely dominated by primordial H/He. Although, mass and radius are insufficient to determine the composition of the gas envelopes (uncertainties on Z gas are large), considering the evolution of the atmospheres can inform us on the nature of the gas as stellar irradiation drives atmospheric escape and can efficiently erode thin primordial atmospheres of H/He on short time-scales (Dorn & Heng 2018). In consequence, primordial H/He gas can be excluded for atmospheres that are too thin in order to be stable against evaporative loss.…”
Section: Interior Characterisationmentioning
confidence: 99%
“…In consequence, primordial H/He gas can be excluded for atmospheres that are too thin in order to be stable against evaporative loss. Following the work of Dorn & Heng (2018), there is a theoretical minimum threshold thickness for a primordial H/He atmosphere, which corresponds to the amount of gas (in H 2 ) that is lost on a short time-scale (here we use 100 Myr). For TOI-402.01, assuming solar-like X-ray and UV (XUV) flux emitted by the host star, this threshold thickness is 0.12 R p and thus larger than the inferred thicknesses (r env = 0.01 +0.05 −0.01 R p ).…”
Section: Interior Characterisationmentioning
confidence: 99%